2017
DOI: 10.4103/ajm.ajm_17_17
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the health status of Syrian refugee children in a tertiary hospital in Turkey

Abstract: Objective: Migration is a problem affecting all family members, but particularly children. Child refugees are the highest risk group for the health systems of receiving countries. We investigated the health of 104 Syrian child refugees presenting to a tertiary hospital in Turkey. Settings and Design: A retrospective study was conducted in the pediatric clinic. Materials and Methods: The medical files of Syrian refugee children (0–18 years) presenting to Adiyaman University Hospital, Pediatric Clinic between 01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Furthermore, because the rate of tuberculosis has increased in Turkey in 2014, refugees, particularly those living outside of camps, pose a significant health risk. In large cities like Istanbul, Ankara, and Izmir, many refugees live in deplorable conditions and are homeless [ 18 , 19 ]. Furthermore, communicable diseases pose a serious public health threat to both refugees and residents of the host country.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, because the rate of tuberculosis has increased in Turkey in 2014, refugees, particularly those living outside of camps, pose a significant health risk. In large cities like Istanbul, Ankara, and Izmir, many refugees live in deplorable conditions and are homeless [ 18 , 19 ]. Furthermore, communicable diseases pose a serious public health threat to both refugees and residents of the host country.…”
Section: Methodsmentioning
confidence: 99%
“…In a large cohort study from Germany, refugee reception showed that medical attention was particularly needed for infants and young refugee children for acute complaints such as infection, cough, fever, or other potentially infectious diseases (Happle et al, 2019). For example, in a study which was conducted in Turkey with 0–5 years old refugee children, half of the sample had iron deficiency anemia (Bucak et al, 2017). It was proposed that refugee children under 5 years old must be specially checked for two preventible conditions, anemia and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly seen comorbidities are related to psychological disorders, such as acute psychological crises or post‐traumatic stress disorder (Pfortmueller et al, 2016). Chronic malnutrition was ascertained in 60.7% of Syrian patients admitted to hospitals (Bucak et al, 2017). One of the other most important problems for both the host communities and refugees is the increase in communicable disease cases (Ekmekci, 2017).…”
Section: Background To the Current Studymentioning
confidence: 99%